Dike propagation energy balance from deformation modeling and seismic release. Issue 11 (14th June 2017) - Bonaccorso, Alessandro; Aoki, Yosuke; Rivalta, Eleonora
Abstract: Magma is transported in the crust mainly by dike intrusions. In volcanic areas, dikes can ascend toward the free surface and also move by lateral propagation, eventually feeding flank eruptions. Understanding dike mechanics is a key to forecasting the expected propagation and associated hazard. Several studies have been conducted on dike mechanisms and propagation; however, a less in‐depth investigated aspect is the relation between measured dike‐induced deformation and the seismicity released during its propagation. We individuated a simple x that can be used as a proxy of the expected mechanical energy released by a propagating dike and is related to its average thickness. For several intrusions around the world (Afar, Japan, and Mount Etna), we correlate such mechanical energy to the seismic moment released by the induced earthquakes. We obtain an empirical law that quantifies the expected seismic energy released before arrest. The proposed approach may be helpful to predict the total seismic moment that will be released by an intrusion and thus to control the energy status during its propagation and the time of dike arrest. Plain Language Summary: Dike propagation is a dominant mechanism for magma ascent, transport, and eruptions. Besides being an intriguing physical process, it has critical hazard implications. After the magma intrusion starts, it is difficult to predict when and where a specific horizontal dike is going to halt and what its final length will be. In our study, we singled an equation that can be used as a proxy of the expected mechanical energy to be released by the opening dike. We related this expected energy to the seismic moment of several eruptive intrusions around the world (Afar region, Japanese volcanoes, and Mount Etna). The proposed novel approach is helpful to estimate the total seismic moment to be released, therefore allowing potentially predicting when the dike will end its propagation. The approach helps answer one of the fundamental questions raised by civil protection authorities, namely, "how long will the eruptive fissure propagate?" Key Points: The study investigated the relationship between the deformation induced by dike propagation leading to eruptions and the released seismic energy We individuated a simple equation that can be used as a proxy of the expected mechanical energy released by a propagating dike that is related to its average thickness We obtained an empirical law that quantifies the seismic moment released by a dike intrusion, thus providing a tool to control the energy status during its propagation